Differentiation between control subjects and patients with chronic spontaneous urticaria based on the ability of anti-IgE autoantibodies (AAbs) to induce FcεRI crosslinking, as compared to anti-FcεRIα AAbs - Satoshi Izaki; Shota Toyoshima; Takahiro Endo; Kazuko Kanegae; Satoshi Nunomura; Jun-ichi Kashiwakura; Tomomi Sasaki-Sakamoto; Ryosuke Nakamura; Haruyo Akiyama; Chisei Ra; Koremasa Hayama; Tadashi Terui; et al. (Allergology International, 2019)
Background: The reported prevalences of IgG autoantibodies (AAbs) to FcεRIα and IgE in sera from patients with chronic spontaneous urticaria (CSU) have varied, and these AAbs are also often observed in healthy control subjects. Regarding the histamine release activity of purified IgG from patients with CSU, the number of examined patients has been small. Thus, we sought to determine the prevalence and FcεRI crosslinking ability of these AAbs in a large number of patients with CSU and non-atopic control (NC) subjects. Methods: We compared the concentrations of anti-IgE and anti-FcεRIα AAbs and the abilities of these AAbs to cause FcεRI aggregation in patients with CSU (n = 134) and NC subjects (n = 55) using ELISA and an in vitro elicitation test, respectively. Results: The concentration of anti-IgE AAbs was significantly different between the NC subjects and the CSU patients (P < 0.0001, cutoff value: 0.558 μg/mL), whereas the concentration of anti-FcεRIα AAbs was not. A significant difference in the duration of illness was noted between patients with lower and those with higher concentrations of anti-IgE AAbs relative to the cutoff value. The abilities of anti-IgE AAbs, but not anti-FcεRIα AAbs, to induce FcεRI crosslinking were significantly higher in CSU patients than in NC subjects (P = 0.0106). Conclusions: In the Japanese population of CSU patients studied, the ability of the anti-IgE AAbs to induce FcεRI crosslinking differed significantly between NC subjects and CSU patients, suggesting the involvement of anti-IgE AAbs in the pathogenesis of CSU in the Japanese population. Keywords: Autoantibody, Basophil/mast cell, FcεRIα, Immunoglobulin E, Urticaria